Brasil um país laico: uma análise da posição da igreja católica sobre as pesquisas da área da genética - Pinheiro, Flawbert Farias Guedes (2011)
This work presents the ventilation: Brazil a Secular Country: an analysis of the Catholic Church's position on research in the field of Genetics. In it he analyzes it, even though Brazil is a Secular Country, Morals and Ethics of the Catholic Church s hinder advances in Genetics, especially with regard to norms and regulations of the results of this research field. To this end, we analyzed the Concordat Brazil/Vatican and the Instruction Dignitas personae above some issues of Bioethics. It was developed a bibliographic search and exploratory documentary, whose analysis of qualitative data, was made in view of Oliveira (2007). The discussion is based on the works of authors such as Giovanni Filoramo and Carlo Prandi (2007), Glória das Neves Dutra Escarião (2006), Marília de Franceschi Neto Domingos (2009), C. E. Gargett (2004), Gerson Odilon Pereira (2010), Andrea Pacheco Pacífico e Gerson Odilon Pereira (2010) e Mayana Zatz (2011), to treat religion and religious phenomena, the human discomfort, due to Globalization, Secularism; Laicity and Secular State; the dilemma of research with embryonic stem cells, the techniques of in vitro fertilization and embryos supernumerary or surplus them resulting; and therapeutic cloning. This research shows that, before the scenario curtailed by the progress of biotechnology, issues hitherto unpredictable society, today, needs urgent and coherent responses in order, if it, is true that scientific progress can bring benefits to humanity, is too, he can build biological weapons that can decimate it, why should always be considered the risks that these innovations may contain.